A study on emerging management practices of renewable energy companies after the outbreak of Covid-19:using an interpretive structural modeling (ISM) approach - Rafiq, Muhammad (2021)
The role of management practices in the success of renewable energy organizations is not negligible because management practices are the backbone of any organization. Energy organizations are facing drastic environmental issues; therefore, the sector inevitably requires environment- friendly production, which is only possible through the deployment of concurrent management practices because sluggish management practices lead to dormancy and inadequate performance. This study investigates the emerging management practices that will enable the renewable energy sector to fulfill the current demands of the market, especially after the outbreak of the Covid-19 pandemic. This research deployed a qualitative research methodology that is grounded in the interpretivism research paradigm. Interpretive structural modeling (ISM) was applied due to the extent of its logical thinking, and its ability to address complex issues and disseminate results precisely. Data were collected through primary (structured and unstructured interviews) and secondary sources (literature reviews published in the last 10 years). Interviews of top- and middle-level managers working in the renewable energy sector of developing countries were conducted. The findings of the study postulate that the implementation of knowledge management practices and policy changes are the key influencing factors to achieve sustainable organizational performance. Decentralization also has the potential to influence and navigate the organizational performance of energy companies. The findings of the research advocate innovative practices for the energy sector that influence organizational performance. The qualitative findings of the study suggest that emerging practices, including knowledge management practices and decentralization, may proliferate organizational growth and development. The novel framework of the study implies that organizations should work progressively in deploying emerging management practices such as establishing a central response hub to avoid delays under the umbrella of resilience leadership.